Application Of Cognitive Learning Theory In Improving Students' Critical Thinking Skills - Harahap, Narti (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The ability to think critically is one of the essential skills in the modern era, especially in facing the challenges of a world full of information. This research aims to analyze the impact of applying cognitive learning theory on the development of critical thinking skills in class 6D MIN 1 Batam students. The research uses qualitative methods with a case study approach, involving observation, interviews and document analysis. The research results show that the implementation of cognitive learning theory has a positive impact on students' critical thinking skills. This approach allows students to be more active in the learning process through group discussions, case study analysis, and reflection, which encourages their ability to analyze, evaluate, and solve problems logically. Improving critical thinking skills is also accompanied by strengthening social skills, such as collaboration and communication. However, there are challenges in the form of limited time and the diversity of student abilities. Teachers apply differentiation strategies and various learning methods to overcome these challenges. This research concludes that cognitive learning theory is effective in improving students' critical thinking skills and creating a more interactive learning environment. Research recommends teacher training and provision of adequate resources to support more optimal implementation. These findings demonstrate the importance of cognitive-based learning approaches in the education system to equip students with 21st century skills.